Political Crisis Following the Adoption of the Third Universal in the Context of Land Issues in Ukraine. - Voronyanskyi, Oleksandr (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
Research aim. This article explains the internal economic and social preconditions for the governmental crisis that followed the adoption of the Third Universal by the Central Rada, considering systemic economic factors that shaped the stance of the Ukrainian government regarding land reforms at that time. Methodology of the research. The analysis of internal crisis factors focuses on various elements, including the nature of landlord estates in Ukrainian governorates at the beginning of the 20th century, the distribution of land among rural households unable to engage in commercial production due to land scarcity and lack of resources to sustain draft animals, as well as the programmatic positions of Ukrainian socialist-oriented parties regarding land reform directions. The scientific novelty. This study demonstrates that the political crisis stemming from the adoption of the Third Universal was triggered by the government’s inability to resolve contradictions between the need to maintain a commodity-based agricultural system–primarily upheld by large, capitalist-style privately-owned estates closely linked to financial capital, which occupied a significant portion of Ukraine’s agricultural lands–and the need to allocate land to peasants as a basic means of subsistence for rural families. The article highlights that, according to the socialist parties’ agendas, one approach considered by the Central Rada and its government for resolving these contradictions was to establish collective farms on the basis of landlord estates. Conclusions. By the early 20th century, large-scale landownership in Ukraine had already acquired a capitalist nature in terms of both organization and integration into market relations. However, the limited volume of land available for redistribution made it impossible to allocate enough land for all peasants to conduct commercial farming. Consequently, land reform based on the redistribution of landlord lands neither had an anti-feudal character, promoted capitalist relations, nor could it mitigate the severe agrarian crisis. Under these conditions, the leadership of the General Secretariat for Land Affairs of the Central Rada pursued a policy aimed at preserving large, capitalized estates of a latifundial type, which conflicted with the mass peasant movement advocating for an egalitarian redistribution of land ownership. As a result, the Central Rada lost its primary social base–the Ukrainian peasantry–which ultimately led to its removal from the historical stage.